Ответы и объяснения

2015-01-01T17:00:59+03:00
Решить уравнение: \lg(5{\textsl{x}}-4)=\lg(1-{\textsl{x}})
     Решение:

Отметим ОДЗ:

 \left \{ {{1-{\textsl{x}}>0} \atop {5{\textsl{x}}-4>0}} \right. \to \left \{ {{{\textsl{x}}<1} \atop {{\textsl{x}}> \frac{4}{5} }} \right.  \\  \\ {\textsl{x}} \in ( \frac{4}{5} ;1)

Воспользуемся свойством логарифмов
\lg(5{\textsl{x}}-4)=\lg(1-{\textsl{x}}) \\ 5{\textsl{x}}-4=1-{\textsl{x}} \\ 5{\textsl{x}}+{\textsl{x}}=4+1 \\ 6{\textsl{x}}=5 \\ {\textsl{x}}= \frac{5}{6}

Ответ: 
{\textsl{x}}= \frac{5}{6}